1998
DOI: 10.1007/s004390050646
|View full text |Cite
|
Sign up to set email alerts
|

A novel point mutation in an acceptor splice site of intron 32 (IVS32 A -12 →G) but no exon 3 mutations in the glycogen debranching enzyme gene in a homozygous patient with glycogen storage disease type IIIb

Abstract: Genetic deficiency of the glycogen-debranching enzyme (debrancher) causes glycogen storage disease type III (GSD III), which is divided into two subtypes: IIIa and IIIb. In GSD IIIb, glycogen accumulates only in the liver, whereas both liver and muscles are involved in GSD IIIa. The molecular basis for the differences between the two subtypes has not been fully elucidated. Recently, mutations in exon 3 of the debrancher gene were reported to be specifically associated with GSD IIIb. However, we describe a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Patient 12 (female, age 41 years) had type IIIb and was compound heterozygous for the novel p.Arg343Trp mutation and c.4260-12A>G in intron 32. c.4260-12A>G was previously described and associated with IIIb as well as IIIa (Okubo et al 1998;Shaiu et al 2000). This patients' phenotype was severe IIIb and a case report on her was published after she received an orthotopic liver transplantation after being diagnosed with liver cirrhosis (Haagsma et al 1997).…”
Section: Discussionmentioning
confidence: 79%
“…Patient 12 (female, age 41 years) had type IIIb and was compound heterozygous for the novel p.Arg343Trp mutation and c.4260-12A>G in intron 32. c.4260-12A>G was previously described and associated with IIIb as well as IIIa (Okubo et al 1998;Shaiu et al 2000). This patients' phenotype was severe IIIb and a case report on her was published after she received an orthotopic liver transplantation after being diagnosed with liver cirrhosis (Haagsma et al 1997).…”
Section: Discussionmentioning
confidence: 79%
“…We have reported the heterogeneity of AGL mutations in Japan. Eleven different mutations have been identified in our studies (Horinishi et al 2002;Okubo et al 1996Okubo et al , 1998Okubo et al , 1999Okubo et al , 2000a. Lucchiari et al (2002) discovered genetic heterogeneity in Italian patients also, although one splicing mutation (IVS21+1G>A) accounts for 28%.…”
Section: Introductionmentioning
confidence: 68%
“…Those studies revealed that the spectrum of AGL mutations in GSD III patients depends on ethnic grouping. For example, specific mutations were prevalent in Jewish GSD III patients (Parvari et al 1997) and in an isolated region such as the Faroe Islands (Santer et al 2001) because of founder effect, while heterogeneous mutations were found in Japanese patients (Horinishi et al 2002;Okubo et al 1996Okubo et al , 1998Okubo et al , 1999Okubo et al , 2000a. In Caucasian and Italian populations a few mutations accounted for a quarter of GSD III patients, but the rest of the mutations were heterogeneous (Lucchiari et al 2002a, b;Shen and Chen 2002).…”
Section: Introductionmentioning
confidence: 99%